La explotación laboral de niños, niñas y adolescentes en el Ecuador - Atencio-González, Rously Eedyah; López-Sánchez, Gabriel Alexander; Veliz-León, Priscila Elisa (IUSTITIA SOCIALIS, 2021)
La explotación laboral de niños, niñas y adolescentes en el Ecuador